On the existence of discontinuous limit cycles for one system of differential equations with pulse influence - Gorbachuk, T. V.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For one system of differential equations with pulse influence, we establish conditions under which a positive root of the equation for stationary amplitudes obtained from equations of the first approximation generates a discontinuous limit cycle. We construct improved first approximations for the system under consideration.